Putusan Bebas Terdakwa Tindak Pidana Korupsi oleh Majelis Hakim Pengadilan Negeri Palembang - Albadrul Maniru (Jurnal Hukum Lex Generalis, 2025)
This study examines the implementation and legal consequences of acquittal verdicts in corruption cases by the Panel of Judges at the Palembang District Court. Corruption is categorized as an extraordinary crime with a significant impact on the state and society. However, in several instances, defendants have been acquitted due to insufficient legal evidence. Using a normative-juridical approach, this research analyzes the legal reasoning of the judges and its implications for anti-corruption efforts in Indonesia, particularly regarding the independence of the judiciary and public trust in the judicial system.